The economic crisis and lifestyle changes: a survey on frequency of use of medications and of preventive and specialistic medical care, in the Marche Region (Italy) - Grappasonni, Iolanda; Scuri, Stefania; Tanzi, Elisabetta; Kracmarova, Lenka; Petrelli, Fabio (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: In the words of one observer, one of the many effects of the economic downturn has been a “health system shock” marked by reductions in the availability of healthcare resources and increases in the demand for health services. The financial situation influences negatively the low-income family groups, particularly those who normally use the government provided primary prevention services. The goal of this study was to assess the impact of the global recession on the use of medicines and medical investigation recession in different areas of the Marche Region. Methods: An anonymous questionnaire prepared by the National Institute of Statistics, modified and validated by the University of Camerino, has been distributed to junior highschool students of Central Italy to provide a statistically representative sample of families. The questionnaire has been administered in 2016-2017. Results: This article examines the results about healthcare habits, specifically, regarding medicines and medical examinations. Data obtained emphasize a reduction in the use of nonsteroidal anti-inflammatory drugs (NSAIDs). The parents category showed the higher change in medicines use (72.9%). Comparing the data of the Fabriano area with that of the Civitanova Marche area, Fabriano reported a greater reduction in the frequency of taking medicine. Concerning the medical examinations, half of the respondents (62.5%), indicated that they and their family members have regular medical check-up. Conclusions: Respondents who admitted that the economic crisis had reduced their quality of life indicated that the parents were the ones who had experienced the greatest change. This is confirmed by the information on the reduced frequency of medicine use, which affected the parents more than the children, whom they sought to protect and safeguard the most. This reduction was most marked in the Fabriano area. In contrast, in the Civitanova Marche area, with different socioeconomic characteristics, an increase in the use of all the categories of medicines was reported. Concerning visits the situation in the Marche Region appears encouraging.